Konsep Integrasi Ilmu dalam Pandangan Ismail Raji Al-Faruqi - Arifuddin, Arifuddin (SYAMIL, 2015)
The development of science grows rapidly. However, this phenomenon raises a huge impact for Muslims. It has been our behaviorÂ  that distinguish between Moslem Science and other knowledge. There is a discriminative treatment against the two types of science. Muslims are divided into those who have positive perception of the Islamic sciences, and negative to other, or vice versa. Based on the reality, Al-Faruqi says that there is no other way to raise Islam, except to reassess the culture of Islamic scholarship in the past, present and modern scholarship as well, and then process them into scientific to be a mercy to the world through what called "integrated science". From the background, the purposes of this study are 1) To know the concept of science integration Ismail Raji al-Faruqi sight. 2) To know the method implementation of the science integration concept in Ismail Raji al-Faruqi sight. This research uses descriptive-analysis method. Descriptive method tries to explain the concepts of Ismail Raji al-Faruqi thought about the science integration. While the analysis technique used is a combination among deductive, inductive, and interpretation. After the research completed, it could be concluded that the Science Integration Concepts in Ismail Raji al-Faruqi sight shows us that science is not value-free and must be based on the method of monotheism. Tauhid principle should be the basic or the main foundations in the development of science in Islam. So that, it shows us to the development of community beneficial. The idea of science Islamisation is one solution to overcome the people problems. The ideas are implemented in 12- work plan steps in Science Islamisation program.